1965
DOI: 10.1128/jb.90.2.456-466.1965
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Ribosomes to Cytoplasmic Reticulum of Bacillus megaterium

Abstract: Binding of ribosomes to cytoplasmic reticulum of Bacillus megaterium. J. Bacteriol. 90:456-466. 1965.-As many as 60% of the cellular ribosomes are bound to membrane "ghosts" in lysozyme lysates in 0.02 M Mg2+. Bound ribosomes labeled with C'4-uracil do not exchange with added unlabeled ribosomes, even after disruption of the cell membrane by sonic treatment. Electron micrographs of thin sections of ghosts, or of fragments produced by sonic disruption of protoplasts, indicate that the ribosomes are distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1966
1966
1998
1998

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…These fine fibrils of approximately 15 A thickness possibly originate from plasma membrane and extend all over the cell, forming a meshwork. Similar observations have been made by others (17).…”
Section: Fig 1 Listeria Monocytogenes Cell Harvested In the Log Phasupporting
confidence: 92%
“…These fine fibrils of approximately 15 A thickness possibly originate from plasma membrane and extend all over the cell, forming a meshwork. Similar observations have been made by others (17).…”
Section: Fig 1 Listeria Monocytogenes Cell Harvested In the Log Phasupporting
confidence: 92%
“…Although the possibility of a fibrillar cytoplasmic network was recognized many years ago (145,163), nowadays it seems to be generally agreed that E. coli does not contain a cytoskeleton. Eukaryotic structures like microfilament bundles, microtubules, and intermediate filaments have not been detected.…”
Section: Does E Coli Have a Cytoskeleton?mentioning
confidence: 99%
“…These observations conflicted with the original report of Schlessinger (19), who reported that at least 25% of the ribosomes of B. megaterium were bound to protoplast membranes as polyribosomes capable of controlling protein synthesis. This apparent discrepancy has now been resolved by ultrastructural studies indicating a reticular matrix extending through the cytoplasm of B. megaterium to which the ribosomes are bound (20). Upon lysis of the cell, this reticulum may fractionate with protoplast membranes.…”
mentioning
confidence: 99%